PERBANDINGAN ABNORMALITAS KONDUKSI SARAF PADA SUBJEK DIABETES MELITUS DENGAN ULKUS DAN TANPA ULKUS - , Fajar Maskuri ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Foot ulcer is by far the most frequently found complication of diabetes, occuring in 15% of the diabetic population, and is the most popular cause of hospital admission and lower extremity amputation of diabetic patients. The risk factors of diabetic ulcers is multifactorial, peripheral neuropathy being the most dominant factor. The severity of the neuropathy may be measured by means of electrodiagnostics. This study is aimed to compare the electrodiagnostic abnormalities (the values of motor nerves conduction studies [MCS] and sensory nerves conduction studies [SCS]) in diabetic subjects with and without ulcers, and assessing the electrodiagnostic variable most associated with the prevalence of diabetic ulcers. A cross sectional study was used on diabetic subjects that underwent an electrodiagnostic studies. Subjects went through a MCS and SCS and were then subjected to statistical analysed. Fifty-six subjects included in this study consisted of 23 subjects with diabetic ulcers and 33 subjects without diabetic ulcers. For MCS, there were significantly differences in median (38,73Â±9,99 vs 47,15Â±8,77 m/s, p=0,001) and tibial (28,76Â±8,48 vs 34,00Â±7,33 m/s, p=0,030) NCV between diabetic subjects with and without foot ulcers. Distal latency, distal amplitude and proximal amplitude values did not show any significant difference between the two groups. The value of NCV <80% increases the risk of diabetic ulcers (prevalence ratio [95% CI]) 3,28 (1,08â9,99). The study concludes, NCV slowing on diabetic subjects with ulcers is more severe than the diabetic subjects without ulcers, and the NCV abnormality is more closely associated with diabetic ulcers.